Biodiversity of entomonematodes parasitizing soil pest white grubs (Scarabaeidae) of Buenos Aires, Argentina - Camino, Nora Beatriz (2014)
This work was carried out between 2006-2010 in wheat fields of the Pampas, Argentina, in order to determine species of nematode parasites and pathogens of white grubs, soil major pest. Samples were taken with shovel in randomly selected sites. Nymphs of Diloboderus abderus and Cyclocephalla signaticollis (Scarabaeidae) were collected. Thirteen species of nematodes belonging to 5 families (Mermithidae, Thelastomatidae, Travassonematidae, Diplogasteridae and Rhabditidae) were determined. The richness species values were 1 for Cyclocephalla signaticollis and 12 for Diloboderus abderus. The thelastomatids and rhabdítids were the largest group of nematodes, with a total of 3 species each. The thelastomátids were very prevalent with infections exceeded 60%, followed by diplogasterids which reached 36%. The mermítids were less prevalent with values close to 10%. The family Travossonematidae was the one with the lowest abundance (0.32). Knowledge of nematode community will be a great ability to interpret host-parasite relationships and in many cases determine those species pest potential bioreguladoras important agents in agricultural areas of Argentina. This study provides for the first time to the Pampas region of our country a list of white worms parasitic nematodes.